1993
DOI: 10.1002/ijc.2910540625
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of colon carcinoma into granulation tissue induces an invasive morphotype

Abstract: The stroma surrounding many malignant tumors resembles granulation tissue. To test the hypothesis that such stroma stimulates tumor invasiveness, we compared, by electron microscopy and immunohistochemistry, the growth patterns of CC531 rat colon adenocarcinoma in 2 experimental situations: (i) after transplantation into the undisturbed subcutaneous connective tissue of rats, and (ii) after transplantation into experimentally induced subcutaneous granulation tissue in rats. For the latter experimental situatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
2

Year Published

1994
1994
2003
2003

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 19 publications
1
24
0
2
Order By: Relevance
“…Alteration of the stromal host compartment is due to an imbalance in the cytokine profile, resulting from the oncogenic changes in the cancer cells. Experimental animal models have demonstrated that cancer invasion is stimulated by the wound-healing stroma [9]. This observation suggests that growth factors implicated in wound healing such as transforming growth factor-β1 (TGF-β1 = TGF-β) [29] and platelet-derived growth factor (PDGF) [30] may also play a role in changing the stromal host compartment in cancer.…”
Section: The Cancer Ecosystemmentioning
confidence: 99%
See 1 more Smart Citation
“…Alteration of the stromal host compartment is due to an imbalance in the cytokine profile, resulting from the oncogenic changes in the cancer cells. Experimental animal models have demonstrated that cancer invasion is stimulated by the wound-healing stroma [9]. This observation suggests that growth factors implicated in wound healing such as transforming growth factor-β1 (TGF-β1 = TGF-β) [29] and platelet-derived growth factor (PDGF) [30] may also play a role in changing the stromal host compartment in cancer.…”
Section: The Cancer Ecosystemmentioning
confidence: 99%
“…Cancer invasion is stimulated by wounding of the host tissue as demonstrated by rat colon adenocarcinoma cells that were transplanted into experimentally induced subcutaneous granulation tissue and in undisturbed subcutaneous tissue. In the pre-formed granulation tissue the tumours closely resembled invasive colon carcinomas, whereas in the undisturbed subcutaneous tissue the tumour was encapsulated and non-invasive [9]. Local factors act also at the site of metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Tumour-associated macrophages recruited by the inflammatory reaction associated with cancer diseases have been suggested to favour or, alternatively, to interfere with the invasive growth of cancer cells (Mantovani et al, 1992;Dingemans et al, 1993;Levine and Saltzman, 1990; Van der Boschet et al, 1992;Orosz et al, 1993;Quin et al, 1993). These conflicting observations are possibly related to the pleiotropic biological effects mediated by cytokines produced by the host in response to tumour invasion and metastasis.…”
mentioning
confidence: 99%
“…As for the mechanism of local recurrence, it should be noted that hepatic recurrence, in rats treated with laser or resection, was always located within or close to granulation tissue. Tissue trauma and healing enhances the take and growth of both circulating and implanted tumour cells, which may be due to local growth factors, angiogenesis and/or clot formation (van den Brenk et al, 1973;Withers and Milas, 1973;Eggermont et al, 1987;Orr and Warner, 1987;Weiss et al, 1988;Murthy et al, 1989;Loizidou et al, 1991;Dingemans et al, 1993). There is a two-to threefold rise in transaminases shortly after laser treatment (Bosman et al, 1991;Masters et al, 1992;van Hillegersberg et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…These unwanted effects of surgery may be caused, at least partly, by immunosuppression and by the release of growth factors involved in tissue healing (Eggermont et al, 1987;Loizidou et al, 1991;Panis et al, 1992;Pollock et al, 1992;Dingemans et al, 1993;Oka et al, 1994;Slooter et al, 1995). One of the advantages of local tissue destruction is that the trauma is small compared with surgery.…”
mentioning
confidence: 99%